The Pontic Greeks, from Pontus to the Caucasus, Greece and the diaspora - Michel Bruneau (Revue de Géographie Alpine)
From the Byzantine period until the beginning of the 20th century, the Pontic Greeks, from the shores of the Black Sea, lived in the mountain areas of the Pontic Alps, where they were able to preserve their language and/or their orthodox religion on the eastern borders of first the Byzantine and then the Ottoman Empire. Like many mountain people, the Pontic Greeks moved a lot, in their case in the direction of the Caucasus and Russia. The exchange of populations between Turkey and Greece in 1923 resulted in their settling as refugees on the northern Balkan borders of their new homeland. Later, after the Second World War, the population of Pontic Greeks became dispersed in a world diaspora. In response to these developments, they created a very rich “iconography” (in the sense used by Jean Gottmann), which enabled them to transmit their identity from one generation to the next by establishing places of remembrance in the areas in which they settled. The construction of a transnational network, within which they regularly created mobile and symbolic frontiers with the help of this iconography and the places of remembrance it adorned, enabled them to reproduce their ethnic identity. This helped them resist assimilation by the host societies, be they Greek or foreign. Constant reference to the territory and mountain places of their origins has forged links with the border zones where they now live and with their iconography that underpins the mobile frontiers, which in a diaspora distinguishes them from other Greeks and the citizens of their host country.